Loss of glucocorticoid rhythm induces an osteoporotic phenotype in female mice. Issue 10 (30th September 2021) - Schilperoort, Maaike; Kroon, Jan; Kooijman, Sander; Smit, Annelies E.; Gentenaar, Max; Mletzko, Kathrin; Schmidt, Felix N.; van Ruijven, Leo; Busse, Björn; Pereira, Alberto M.; Appelman‐Dijkstra, Natasha M.; Bravenboer, Nathalie; et al.
Abstract: Glucocorticoid (GC)‐induced osteoporosis is a widespread health problem that is accompanied with increased fracture risk. Detrimental effects of anti‐inflammatory GC therapy on bone have been ascribed to the excess in GC exposure, but it is unknown whether there is also a role for disruption of the endogenous GC rhythm that is inherent to GC therapy. To investigate this, we implanted female C57Bl/6J mice with slow‐release corticosterone (CORT) pellets to blunt the rhythm in CORT levels without inducing hypercortisolism. Flattening of CORT rhythm reduced cortical and trabecular bone volume and thickness, whilst bone structure was maintained in mice injected with supraphysiologic CORT at the time of their endogenous GC peak. Mechanistically, mice with a flattened CORT rhythm showed disrupted circadian gene expression patterns in bone, along with changes in circulating bone turnover markers indicative of a negative balance in bone remodelling. Indeed, double calcein labelling of bone in vivo revealed a reduced bone formation in mice with a flattened CORT rhythm. Collectively, these perturbations in bone turnover and structure decreased bone strength and stiffness, as determined by mechanical testing. In conclusion, we demonstrate for the first time that flattening of the GC rhythm disrupts the circadian clock in bone and results in an osteoporotic phenotype in mice. Our findings indicate that at least part of the fracture risk associated with GC therapy may be the consequence of a disturbed GC rhythm, rather than excess GC exposure alone, and that a dampened GC rhythm may contribute to the age‐related risk of osteoporosis. Abstract : Negative effects of glucocorticoid (GC) therapy on bone have been ascribed to the excess in GC exposure, but it is unknown whether disruption of endogenous GC rhythm also plays a role. Here, we show that flattening of the GC rhythm without increasing GC exposure in mice disrupts the circadian clock in bone and results in an osteoporotic phenotype, whilst bone quality is maintained in mice injected with supraphysiologic GCs at the time of their endogenous GC peak. These data indicate that disruption of GC rhythm may underlie age‐related osteoporosis, and could in itself contribute to negative effects of GC therapy on bone.